Impact of the steepness of the slope on the biomechanics of World Cup slalom skiers - Supej, M.; Hebert-Losier, K.; Holmberg, H. C. (International Journal of Sports Physiology and Performance, 2015)
Purpose: Numerous environmental factors can affect alpine-ski-racing performance, including the steepness of the slope. However, little research has focused on this factor. Accordingly, the authors` aim was to determine the impact of the steepness of the slope on the biomechanics of World Cup slalom ski racers. Methods: The authors collected 3-dimensional kinematic data during a World Cup race from 10 male slalom skiers throughout turns performed on a relatively flat (19.8°) and steep (25.2°) slope under otherwise similar course conditions. Results: Kinematic data revealed differences between the 2 slopes regarding the turn radii of the skis and center of gravity, velocity, acceleration, and differential specific mechanical energy (all P < .001). Ground-reaction forces (GRFs) also tended toward differences (P = .06). Examining the time-course behaviors of variables during turn cycles indicated that steeper slopes were associated with slower velocities but greater accelerations during turn initiation, narrower turns with peak GRFs concentrated at the midpoint of steering, more pronounced lateral angulations of the knees and hips at the start of steering that later became less pronounced, and overall slower turns that involved deceleration at completion. Consequently, distinct energy-dissipation-patterns were apparent on the 2 slope inclines, with greater pregate and lesser postgate dissipation on the steeper slope. The steepness of the slope also affected the relationships between mechanical skiing variables. Conclusions: The findings suggest that specific considerations during training and preparation would benefit the race performance of slalom skiers on courses involving sections of varying steepness.